Preoperative and perioperative factors that predict graft failure 1 year after Descemet membrane endothelial keratoplasty - Lucas Mastrangelo; Jules Leterrier; Christophe Goetz; Yinka Zevering; Jean-Marc Perone (PLoS ONE, 2026)
Purpose To identify pre/perioperative factors that predict graft failure after Descemet membrane endothelial keratoplasty (DMEK). Methods This retrospective cohort study included consecutive eyes that underwent DMEK in 2015–2023 in a regional referral hospital and were followed for at least 12 months. DMEK-graft failure was defined as need for regrafting during follow-up. Univariable analysis of graft-failure associations with 20 covariates was performed. Hierarchical multivariable analysis was conducted for DMEK-graft failure with covariates whose univariable-analysis p-values were ≤0.15. Posthoc univariable analyses were performed to elucidate the mechanisms by which covariates promoted DMEK-graft failure. Results 171 eyes (129 patients) with mostly Fuchs endothelial corneal dystrophy (94%) were included. Median (range) follow-up was 24 (12–29) months, during which 15 grafts (9%) failed. On univariable analyses, graft failure associated with eight variables, including long (≥25 mm) preoperative axial length (AXL): 40% of graft-failure eyes had AXL ≥ 25 mm vs. 13% for graft-success eyes (p = 0.01). On multivariable analysis, graft failure was predicted by AXL ≥ 25 mm (OR=5.70; 95%CI = 1.27–25.68; p = 0.02), younger graft-donor age (OR=0.93; 95%CI = 0.88–0.99; p = 0.02), graft-unscrolling/positioning difficulties (OR=6.93; 95%CI = 1.58–30.48; p = 0.01), and major graft detachment (OR=6.28; 95%CI = 1.36–28.96; p = 0.02). The model accounted for 14% of total graft-failure variance. Posthoc univariable analysis showed that eyes with AXL ≥ 25 experienced graft-unscrolling/positioning difficulties more often than shorter eyes (27% vs. 10%, p = 0.0497). Conclusions Eyes with long AXL (≥25 mm) may be more prone to DMEK-graft failure than shorter eyes. This may reflect the deep anterior chamber, which can complicate graft unscrolling and/or graft positioning. The additional graft handling may induce endothelial-cell loss and subsequent graft failure. Younger donor age weakly predicted DMEK-graft failure, possibly due to tighter scrolling of younger grafts. Major graft detachment strongly predicted DMEK-graft failure. This could reflect surgical and/or rebubbling-induced endothelial damage and/or pre-existing graft weakness.